Factors affecting the overall hiring process and employee satisfaction: A study on Sheba Platform Limited - Surovi, Anika Teheseen (Brac University, 2023)
This internship report is submitted in partial fulfillment of the requirements for the degree of Bachelor of Business Administration, 2020.